Glycosylated extracellular vesicles released by glioblastoma cells are decorated by CCL18 allowing for cellular uptake via chemokine receptor CCR8. Issue 1 (13th March 2018) - Berenguer, Jordi; Lagerweij, Tonny; Zhao, Xi Wen; Dusoswa, Sophie; van der Stoop, Petra; Westerman, Bart; de Gooijer, Mark C.; Zoetemelk, Marloes; Zomer, Anoek; Crommentuijn, Matheus H. W.; Wedekind, Laurine E.; López‐López, Àlan; et al.
ABSTRACT: Cancer cells release extracellular vesicles (EVs) that contain functional biomolecules such as RNA and proteins. EVs are transferred to recipient cancer cells and can promote tumour progression and therapy resistance. Through RNAi screening, we identified a novel EV uptake mechanism involving a triple interaction between the chemokine receptor CCR8 on the cells, glycans exposed on EVs and the soluble ligand CCL18. This ligand acts as bridging molecule, connecting EVs to cancer cells. We show that glioblastoma EVs promote cell proliferation and resistance to the alkylating agent temozolomide (TMZ). Using in vitro and in vivo stem‐like glioblastoma models, we demonstrate that EV‐induced phenotypes are neutralised by a small molecule CCR8 inhibitor, R243. Interference with chemokine receptors may offer therapeutic opportunities against EV‐mediated cross‐talk in glioblastoma.